Exploring Representation-Based Learning Techniques: Toward More Generalized and Self-Optimizing Models - Prakoso Rizky A, Galih; Situmorang, Rohani (Jurnal Teknik Informatika C.I.T Medicom, 2025)
Representation-based learning has become a foundational pillar of modern machine learning, enabling models to extract meaningful structure from complex, high-dimensional data. This study employs a mixed-method research design that integrates theoretical analysis, systematic literature review, and empirical evaluation to investigate the effectiveness of representation-based learning techniques in developing more generalized and self-optimizing machine learning models. Through an integrated review and empirical evaluation, the research investigates how different representation mechanisms influence model generalization, robustness, and adaptability across diverse data modalities. The findings show that deep, self-supervised, and contrastive representations consistently outperform traditional feature engineering, symbolic approaches, and classical statistical models, particularly in low-data and cross-domain scenarios. However, the study also identifies critical challenges including representation collapse, bias in embeddings, high computational overhead, interpretability limitations, and catastrophic forgetting that must be addressed to realize fully autonomous learning systems. In addition to synthesizing advances such as foundation models, multimodal fusion, neuro-symbolic frameworks, and efficient edge-compatible representations, this research proposes a structured framework for evaluating representation quality and outlines conceptual enhancements for self-optimizing learning systems. Overall, the study offers theoretical insights, practical evaluation tools, and forward-looking perspectives that contribute to the development of more generalized, flexible, and self-improving machine learning models capable of meeting the demands of evolving real-world applications.